2010
DOI: 10.1371/journal.pgen.1001134
|View full text |Cite
|
Sign up to set email alerts
|

Orphan CpG Islands Identify Numerous Conserved Promoters in the Mammalian Genome

Abstract: CpG islands (CGIs) are vertebrate genomic landmarks that encompass the promoters of most genes and often lack DNA methylation. Querying their apparent importance, the number of CGIs is reported to vary widely in different species and many do not co-localise with annotated promoters. We set out to quantify the number of CGIs in mouse and human genomes using CXXC Affinity Purification plus deep sequencing (CAP-seq). We also asked whether CGIs not associated with annotated transcripts share properties with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
486
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(527 citation statements)
references
References 59 publications
28
486
0
13
Order By: Relevance
“…Proximal CGIs (close to TSSs) typically are hypomethylated, while distal CGIs (far from TSSs, also known as "orphans") are more likely to be methylated in normal somatic cells. 63 Most p53 ChIP-seq peaks are in proximal although some are in distal CGIs (Figs. 6D and S9).…”
Section: Resultsmentioning
confidence: 99%
“…Proximal CGIs (close to TSSs) typically are hypomethylated, while distal CGIs (far from TSSs, also known as "orphans") are more likely to be methylated in normal somatic cells. 63 Most p53 ChIP-seq peaks are in proximal although some are in distal CGIs (Figs. 6D and S9).…”
Section: Resultsmentioning
confidence: 99%
“…This is true for both TSS and intragenic CGIs, although the proportion of intragenic CGIs marked by H3K4me3 is smaller, with 41% of intragenic CGIs positive for H3K4me3 in embryonic stem (ES) cells compared to 96% of TSS CGIs . Methylated CGIs, on the other hand, do not associate with H3K4me3, reflecting transcriptional silencing at these sites (Meissner et al 2008;Illingworth et al 2010;Maunakea et al 2010). Recent studies have suggested a mechanistic explanation for this phenomenon whereby the protein CFP1 binds to unmethylated CGIs and facilitates recruitment of the SET1 H3K4 methyltransferase complex (Thomson et al 2010).…”
Section: Cgi Methylation Differences Preferentially Occur Within Genementioning
confidence: 99%
“…Gene-body methylation identified 'orphan promoters', which may be used in the early stages of development (30). Hypermethylation of gene-bodies frequently indicates higher levels of gene expression in human tissues and cell types (8,31).…”
Section: Discussionmentioning
confidence: 99%